Direct sensing of host ferric iron by an archetype histidine kinase mediates virulence of an enteric pathogen - Yibei Zhang; Gang Xiao; Haoyuan Ding; Qian Zou; Dan Gu; Jiachen Wen; Yonggang Pei; Rongxian Guo; Qiyao Wang; Xiaohui Zhou (Proceedings of the National Academy of Sciences, 2025)
Two-component system (TCS) histidine kinases enable bacterial pathogens to sense environmental signals and regulate adaptive responses during infection. The EnvZ/OmpR TCS, known for its role in osmolarity/pH-dependent regulation of outer membrane porins across bacterial species, is also a central virulence regulator. However, the environmental cues that activate EnvZ/OmpR to trigger pathogenicity have remained unclear, limiting our understanding of host–pathogen interactions. Here, we demonstrate that in Vibrio parahaemolyticus , a major etiological agent of seafood-associated gastroenteritis, EnvZ functions as a direct ferric iron (Fe 3+ ) sensor governing virulence programs. Fe 3+ -EnvZ interaction triggers kinase phosphorylation and activation, enabling transcriptional control of biofilm formation, swarming motility, and type 3/6 secretion systems. An iron-binding-deficient EnvZ mutant (EnvZ Q103A ) abrogated Fe 3+ responsiveness and downstream signaling pathways. In an infant rabbit infection model, Fe 3+ enhanced V. parahaemolyticus intestinal colonization and virulence through EnvZ/OmpR signaling. This study identifies Fe 3+ as the physiological ligand activating the EnvZ/OmpR virulence regulon and provides insight into how enteric pathogens exploit host-derived iron cues to promote infection.